2016
DOI: 10.1111/1759-7714.12358
|View full text |Cite
|
Sign up to set email alerts
|

Identification of false‐negative and false‐positive diagnoses of lymph node metastases in non‐small cell lung cancer patients staged by integrated 18F‐fluorodeoxyglucose‐positron emission tomography/computed tomography: A retrospective cohort study

Abstract: BackgroundThe aim of this study was to evaluate the diagnostic accuracy of integrated 18 F‐fluorodeoxyglucose positron emission tomography/computed tomography (FDG‐PET/CT) in hilar and mediastinal lymph node (HMLN) staging of non‐small cell lung cancer (NSCLC), and to investigate potential risk factors for false‐negative and false‐positive HMLN metastases.MethodsWe examined the data of 388 surgically resected NSCLC patients preoperatively staged by integrated FDG‐PET/CT. Risk factors for false‐negative and fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 30 publications
1
18
1
2
Order By: Relevance
“…A study 5 found that the false negative rate (1-specificity) of lymph-node metastasis of NSCLC was 13.2%, whereas 45.5% patients were pathologically confirmed as false positive (1-sensitivity), and concluded that lymph node staging using PET-CT is far from being equal to pathological staging. Other findings 6 on the specificity and sensitivity of PET/CT in detecting HMLN metastases in NSCLC patients were 91.0% and 47.4%, respectively. A recent survey 7 showed a wide range of the sensitivity of PET-CT in mediastinal LN staging, varying from 40–86.3%, reported by different research groups 8 9 10 11 12 13 14 15 , which suggested the limitation of PET-CT for the direct assessment of lymph nodes; and therefore, novel methods are needed to be developed to enhance the reliable evaluation of LN staging of NSCLC 7 .…”
mentioning
confidence: 95%
“…A study 5 found that the false negative rate (1-specificity) of lymph-node metastasis of NSCLC was 13.2%, whereas 45.5% patients were pathologically confirmed as false positive (1-sensitivity), and concluded that lymph node staging using PET-CT is far from being equal to pathological staging. Other findings 6 on the specificity and sensitivity of PET/CT in detecting HMLN metastases in NSCLC patients were 91.0% and 47.4%, respectively. A recent survey 7 showed a wide range of the sensitivity of PET-CT in mediastinal LN staging, varying from 40–86.3%, reported by different research groups 8 9 10 11 12 13 14 15 , which suggested the limitation of PET-CT for the direct assessment of lymph nodes; and therefore, novel methods are needed to be developed to enhance the reliable evaluation of LN staging of NSCLC 7 .…”
mentioning
confidence: 95%
“…Early diagnosis of lung cancer allows for the implementation of cancer treatments that may improve the overall survival rate of patients (32)(33)(34). A previous study has demonstrated that CEMRI was able to identify patients who would benefit from bevacizumab and erlotinib treatment compared with CT based on molecular imaging for an earlier diagnosis (35).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Park et al (22) involving 144 patients with cN0 NSCLC who underwent preoperative PET/CT, the frequency of nodal upstaging was 14.3%; the actual frequencies of N1 and N2 involvement were 9.5% and 4.8% respectively, while Casiraghi et al (23) highlighted a 13% rate of occult nodal metastases (29 pN+ of 190 NSCLC cN0 patients). However, among the risk factors for false positives results, the history of lung disease (P<0.001) and central tumor location (P=0.021) were recognized (20).…”
Section: Introductionmentioning
confidence: 97%